Causes of Microbleeding in Alzheimer's: Role of Cerebral Amyloid Angiopathy and Factor Xa Inhibitors - Cynthia; Nugraha, Jusak; Hamdan, Muhammad; Lumempouw, Silvia; Dharma, Rahajuningsih (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
This case report aims to analyze factors that may contribute to the pathophysiological mechanisms underlying microbleeding in Alzheimer’s disease (AD) patients with Deep Vein Thrombosis (DVT), thereby paving the way for appropriate therapeutic interventions and improved patient outcomes. An 80-year-old Indonesian woman, diagnosed with AD and DVT, was admitted to the neurobehavioral clinic on May 16, 2023. Microbleeding was detected in the right cerebellum, right occipital lobe, left caudate nucleus, and left-right frontal cortex based on the Brain MRI. The patient had been treated with factor Xa inhibitors once a day since April 17, 2018, due to DVT. The diagnosis of mild cognitive impairment with bilateral knee osteoarthritis was made on June 13, 2017. Laboratory findings on November 21, 2023, revealed an e-GFR of 36 mL/min/1.73m2, indicating a moderate to severe decline in kidney function. Alzheimer's dementia can cause Cerebral Amyloid Angiopathy (CAA), which can result in clot formation in the brain tissue and around cerebral arteries. This process deteriorates blood flow and impairs the clearance of amyloid beta-peptide (Aβ), leading to Aβ accumulation, microglia activation, synaptic dysfunction, and neuronal death. Decreased cerebral blood flow leads to hypoperfusion, cerebral microvascular infarctions, and microhemorrhages (also known as microbleeds). In elderly patients with Alzheimer's dementia, immobilization often leads to DVT, which is treated with factor Xa inhibitors. However, drug accumulation can occur due to decreased kidney function, potentially causing further microbleeds in the brain. Microbleeding found in this patient might be a consequence of Alzheimer’s pathology and or adverse effects of factor Xa inhibitors.